Heterogeneous Substitutability Preferences - Moritz A. Drupp; Jasper N. Meya; Björn Bos; Simon Disque (CESifo GmbH, 2024)
We study the heterogeneity of preferences regarding the limited substitutability of environmental public goods vis-a-vis private consumption goods and how it affects the economic valuation of environmental public goods. We show theoretically that mean marginal willingness to pay for an environmental public good decreases in society's mean substitutability preference and increases in the heterogeneity of individual-level substitutability preferences. We then introduce an experimental framework to elicit individual-level substitutability preferences for the first time directly, which we apply to study general population preferences concerning the trade-off between market goods and forest ecosystem services. We estimate preference parameters for almost 1,500 individuals and document substantial preference heterogeneity. The majority of individual preferences imply a complementary relationship, with a median elasticity of substitution (complementarity) of around 0.4 (2.5). We show that accounting for heterogeneity in substitutability preferences may considerably increase the societal value attached to environmental public goods. These findings are relevant for environmental cost-benefit analysis and for the comprehensive accounting of public natural capital.
Keywords: Q51; Q56; H41; D64; C99; 330; substitutability; complementarity; heterogeneous preferences; non-market valuation; experiment; donations; public goods; policy appraisal